2022
DOI: 10.4103/heartviews.heartviews_1_22
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Single-Leaflet Device Detachment in a Patient with Marfan Syndrome Treated with Bail-Out Edge-to-Edge Mitral Valve Repair

Abstract: Mitral transcatheter edge-to-edge repair (MTEER) is the first transcatheter technique for mitral valve repair (MVR) in patients with severe mitral regurgitation (MR) who are considered at high risk for surgical intervention. Mitral valve prolapse with subsequent MR is a common manifestation of Marfan syndrome. MTEER has never been reported as a treatment option in such kind of patients. We describe the case of a 30-year-old patient who was known to have Marfan syndrome which was complicated with severe symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, this is the first reported case successfully treated with MitraClip for chronic severe mitral regurgitation after surgery for type A aortic dissection combined with Marfan syndrome. In addition, previous case reports demonstrated that MitraClip was also effective in individuals with postacute type A aortic dissection surgery and Marfan syndrome 11,12 . This shows that MitraClip could be a viable option for these high‐risk patients.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first reported case successfully treated with MitraClip for chronic severe mitral regurgitation after surgery for type A aortic dissection combined with Marfan syndrome. In addition, previous case reports demonstrated that MitraClip was also effective in individuals with postacute type A aortic dissection surgery and Marfan syndrome 11,12 . This shows that MitraClip could be a viable option for these high‐risk patients.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, previous case reports demonstrated that MitraClip was also effective in individuals with postacute type A aortic dissection surgery and Marfan syndrome. 11,12 This shows that MitraClip could be a viable option for these high-risk patients.…”
mentioning
confidence: 96%
“…[ 17 ] One patient had a single leaflet detachment that was successfully managed with stabilization using additional clips. [ 18 ] Only one patient required mitral valve surgery. Overall, our study demonstrated early and sustained improvement in the left ventricular hemodynamics and dimensions, and MR grade post TMVr up to 1-year follow-up with low morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%